Fenomena Kependudukan Dalam Perspektif Ruang Masyarakat di Desa Kemiri Kecamatan Panti Kabupaten Jember - Ulfa, Maria; Solehah, Arifatus (Penerbit Goodwood, 2023)
Purpose: This study aims to analyze and examine population phenomena ranging from fertility, mortality, migration, divorce rates, unregistered marriages, poverty, early marriage, population distribution, population work and the use of contraceptives. Methodology: This type of research includes qualitative descriptive survey research in order to collect data directly from a group of subjects. The data collection techniques are observation, interviews, documentation and literature study. Results: The research findings show that in terms of fertility rates, migration, mortality, divorce, unregistered marriages are low, while early marriage is in the normal category, neither too high nor too low. Unlike the case with the poverty rate, which is still relatively high, this is evidenced by the semi-permanent housing ownership conditions. The phenomenon of population in diverse spaces, of course, requires an effort and alleviation of the problems concerned. Thus, serious attention is needed in the development of Kemiri Village, Panti District, Jember Regency. Limitations: Population phenomena ranging from fertility, mortality, migration, divorce rates, unregistered marriages, poverty, early marriage, population distribution, population work and the use of contraceptives. Contribution: This research can contribute to the surrounding community, especially the Kemiri village community. The scope of this study is related to the geography of the population.